Fiqih Contemporary Health In Perspective Mental Health Of Muslims - Rini Putriani; Haerul iman (CV. AFDIFAL MAJU BERKAH, 2026)
The development of modern life has presented various psychological challenges that have a significant impact on the mental health of humans, including Muslims. Social pressures, changing values, and the complexity of contemporary life have made mental health disorders a serious issue affecting the quality of life of individuals and society. This article aims to analyze the role of contemporary health jurisprudence (fiqh) in developing and maintaining the mental health of Muslims through a normative and contextual approach. This research uses qualitative methods with a library study of classical and contemporary fiqh sources and mental health literature. The results indicate that contemporary health jurisprudence places mental health as an integral part of the goals of Islamic law, particularly in protecting the soul and mind. Health jurisprudence also encourages a holistic approach through the integration of spiritual, psychological, and social values, while also playing a role in reducing the stigma of mental disorders and building collective awareness among Muslims. These findings confirm that contemporary health jurisprudence has a strategic contribution to the sustainable and dignified development of the welfare of Muslims